Rehabilitating coastal agriculture and aquaculture after inundation events: Spatial analysis of livelihood recovery in post-tsunami Aceh, Indonesia. (15th June 2017) - Daly, Patrick; Halim, Agus; Nizamuddin,; Ardiansyah,; Hundlani, Divya; Ho, Ezra; Mahdi, Saiful
Abstract: This paper presents GIS time-series land-use analysis of satellite images to quantify the recovery of rice cultivation and aquaculture following the 2004 Indian Ocean tsunami in coastal communities in Aceh, Indonesia. We supplement this with qualitative data to illustrate the post-disaster challenges faced by residents, and the extent to which coastal communities have adapted to post-tsunami realities. Our analysis shows that the rehabilitation of rice cultivation and aquaculture in areas inundated by the tsunami has been limited by extensive degradation of land, diversion of labor by tsunami mortality and transition to alternative livelihoods, and re-purposing of rice fields for residential use during the reconstruction phase. This is especially prominent in areas where subsistence activities are not the primary source of livelihood. The Aceh case study shows that social, economic, and environmental factors can be stronger determinants of how coastal livelihoods rebound and change following destructive inundation events than livelihood rehabilitation aid. Additionally, our case study suggests the human impact of coastal hazards can be felt outside the physical extent of inundation. Highlights: Marine inundation hazards can cause long-term reduction of subsistence coastal livelihoods. External livelihood reconstruction aid is constrained by local post-disaster contexts. The social impact of coastal hazards can extend inland beyond immediate coastal areas.